2008
DOI: 10.1016/j.saa.2008.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Damage creation in swift heavy ion-irradiated calcite single crystals: Raman and Infrared study

Abstract: a b s t r a c tRaman and Infrared studies were carried out on pristine and 100 MeV Ag 8+ ion irradiated calcite single crystals in the fluence range 1 × 10 11 to 1 × 10 13 ions/cm 2 . Raman and Infrared modes were assigned according to factor theory analysis. It is observed that the intensities of the Raman and infrared bands decrease with increase of ion fluence. The decrease of these bands is attributed to breakage of carbonate ions and other details are discussed.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

1
11
1

Year Published

2009
2009
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 15 publications
(13 citation statements)
references
References 9 publications
1
11
1
Order By: Relevance
“…3a) is postulated to be on account of the ion implantation-induced reorganization of existing defects in the crystal structure, 31 which could have resulted in the observed reduction in dissolution rate as noted above. Previously, Nagabhushana et al 15 showed both reduction in the peak intensity and peak broadening upon ion implantation in calcite for peaks corresponding to the CO 2À 3 group's bending and stretching modes. This was attributed to the breakage of carbonate bond (-C-O-) or changes in the crystallite size due to irradiation-induced volume expansion.…”
Section: Introductionmentioning
confidence: 98%
See 2 more Smart Citations
“…3a) is postulated to be on account of the ion implantation-induced reorganization of existing defects in the crystal structure, 31 which could have resulted in the observed reduction in dissolution rate as noted above. Previously, Nagabhushana et al 15 showed both reduction in the peak intensity and peak broadening upon ion implantation in calcite for peaks corresponding to the CO 2À 3 group's bending and stretching modes. This was attributed to the breakage of carbonate bond (-C-O-) or changes in the crystallite size due to irradiation-induced volume expansion.…”
Section: Introductionmentioning
confidence: 98%
“…For example, for calcite, whereas some studies reported negligible changes both in its atomic structure and dissolution kinetics, 7,14 others indicate an evolution toward an amorphous atomic structure with increasing fluence. 15,16 Analogous studies on dolomite have not been undertaken. Dolomite and calcite exhibit similar structures, wherein layers of carbonate ðCO 2À 3 Þ groups separate layers of different cations (Ca 2+ in calcite, or Ca 2+ and Mg 2+ in dolomite) (see Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Although these techniques are superior but restricted to only Fe ion or paramagnetic species in the system, however any technique based on the vibration modes of any system like Raman and Fourier Transform Infrared (FTIR) spectroscopy may throw more light on the irradiated system. Recent reports show that these techniques have been widely used for studying the irradiation induced effects in single crystals, cordierite [19,20], structural phase transition in materials induced by SHI irradiation [21][22][23], oxygen defects created during irradiation [24,25], etc. Available reports studying the irradiation induced effects in ferrites by these techniques indicate that various vibrational modes exhibit different sensitivities towards irradiation [26][27][28].…”
Section: Introductionmentioning
confidence: 99%
“…Recent reports show that these techniques have been widely used for studying the irradiation induced effects on various class and different properties of materials [6][7][8]. Available reports indicate that various vibrational modes exhibit different sensitivity towards irradiation [9][10][11][12][13] but no discussion has been made on possible cause for such modifications [14].…”
Section: Introductionmentioning
confidence: 99%